Efficacy and safety of sodium oxybate in alcohol-dependent patients with a very high drinking risk level - Brink, Wim van den; Addolorato, Giovanni; Aubin, Henri-Jean; Benyamina, Amine; Caputo, Fabio; Dematteis, Maurice; Gual, Antoni; Lesch, Otto-Michael; Mann, Karl; Maremmani, Icro; Nutt, David; Paille, François; et al. (Addiction biology, 2018)
Medication development for alcohol relapse prevention or reduction of consumption is highly challenging due to methodological issues of pharmacotherapy trials. Existing approved medications are only modestly effective with many patients failing to benefit from these therapies. Therefore, there is a pressing need for other effective treatments with a different mechanism of action, especially for patients with very high (VH) drinking risk levels (DRL) because this is the most severely affected population of alcohol use disorder patients. Life expectancy of alcohol-dependent patients with a VH DRL is reduced by 22 years compared with the general population and approximately 90 000 alcohol-dependent subjects with a VH DRL die prematurely each year in the EU (Rehm et al. ). A promising new medication for this population is sodium oxybate, a compound that acts on GABAB receptors and extrasynaptic GABAA receptors resulting in alcohol-mimetic effects. In this article, a European expert group of alcohol researchers and clinicians summarizes data (a) from published trials, (b) from two new—as yet unpublished—large clinical trials (GATE 2 (n = 314) and SMO032 (n = 496), (c) from post hoc subgroup analyses of patients with different WHO-defined DRLs and (d) from multiple meta-analyses. These data provide convergent evidence that sodium oxybate is effective especially in a subgroup of alcohol-dependent patients with VH DRLs. Depending on the study, abstinence rates are increased up to 34 percent compared with placebo with risk ratios up to 6.8 in favor of sodium oxybate treatment. These convergent data are supported by the clinical use of sodium oxybate in Austria and Italy for more than 25 years. Sodium oxybate is the sodium salt of γ-hydroxybutyric acid that is also used as a recreational (street) drug suggestive of abuse potential. However, a pharmacovigilance database of more than 260 000 alcohol-dependent patients treated with sodium oxybate reported very few adverse side effects and only few cases of abuse. We therefore conclude that sodium oxybate is an effective, well-tolerated and safe treatment for withdrawal and relapse prevention treatment, especially in alcohol-dependent patients with VH DRL.